2020
DOI: 10.1038/s41598-020-78956-1
|View full text |Cite
|
Sign up to set email alerts
|

Anatase TiO2 deposited at low temperature by pulsing an electron cyclotron wave resonance plasma source

Abstract: Photocatalytic surfaces have the potentiality to respond to many of nowadays societal concerns such as clean H2 generation, CO2 conversion, organic pollutant removal or virus inactivation. Despite its numerous superior properties, the wide development of TiO2 photocatalytic surfaces suffers from important drawbacks. Hence, the high temperature usually required (> 450 °C) for the synthesis of anatase TiO2 is still a challenge to outreach. In this article, we report the development and optimisation of an ECWR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In a former article, it was established that, providing a fine tuning of plasma deposition parameters, TiO2 thin films growth occurs following a transition from amorphous to anatase along the thickness [37]. During these studies, the ECWR plasma source has shown its ability to readily deposit anatase layers with high power input [38] and at a high deposition rate [37] (≈10 nm.min -1 ). Also, it is worth mentioning that the proposed process provides very good uniformity of coating thickness (+/-5 % thickness on 5x5 cm 2 surface) and excellent crystalline homogeneity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a former article, it was established that, providing a fine tuning of plasma deposition parameters, TiO2 thin films growth occurs following a transition from amorphous to anatase along the thickness [37]. During these studies, the ECWR plasma source has shown its ability to readily deposit anatase layers with high power input [38] and at a high deposition rate [37] (≈10 nm.min -1 ). Also, it is worth mentioning that the proposed process provides very good uniformity of coating thickness (+/-5 % thickness on 5x5 cm 2 surface) and excellent crystalline homogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the set up descibed in a previous work enabled to deposit anatase TiO2 at Tsub max < 120°C [37], it has been sligthly tweaked in the perspective of lowering the deposition temperature even further. As such, copper substrate holder was used and temperature evolutions were compared with the one obtained previously on a stainless steel substrate holder.…”
Section: Plasma Enhanced Chemical Vapour Deposition Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to any UV illumination, the samples were immersed in the [MB] = 1 µmol l −1 solution then stored under dark condition for one night in order for the adsorption/desorption to reach equilibrium. The 365 nm UV lamps (Herolab UV-8 SL, 365 nm, 2 × 8 W) were then placed at a distance around 8 cm so the measured irradiance was set at 3 mW cm −2 [26,48].…”
Section: Methodsmentioning
confidence: 99%
“…(26,29) Based on XRD results, previous works and literature, we can assume that the bright column ends are associated with crystallization of the film, while the darker contrast can be associated with amorphous-like TiO2. (19,29,33,41) The column size is expected to be much larger than the crystal size, hence the use of the term "polycrystalline columns" through the article. Top-view SEM pictures have been exploited with ImageJ software to extract the density and average area of bright columns arising at the surface and the results are plotted in Figure 5.…”
Section: Morphologymentioning
confidence: 99%